2019
DOI: 10.1029/2019gl084748
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical Shift Toward Longer Dry Spells Associated with Warming Temperatures During Russian Summers

Abstract: This study examines the changing behavior of summer dry spell duration in response to increasing air temperatures at 517 Russian stations during 1966–2010. We found that the frequency distribution of dry spell duration (as represented by histograms) is becoming skewed toward longer dry spells. This asymmetrical shift is accompanied by mean increases in dry spell duration. This asymmetry is also reflected in exponentially higher increasing rates of dry spell duration toward higher percentiles. Consequently, acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 44 publications
0
21
0
1
Order By: Relevance
“…Nonetheless, there are conflicting opinions regarding whether the observed warming is inducing an increase in the length of dry spells, as noted by Ye and Fetzer (2019) in Russia, or whether, as observed by Trenberth et al, (2014), the warming does not prolong the dry event, but that the warming itself may augment the intensity of the episode due to the effect of thermal magnitude. The authors consider that the observed warming has not caused longer-lasting droughts in the area of the Pyrenees, which does not correspond with the findings of Ye and Fetzer (2019). Furthermore, even under an intermediate emissions scenario (RCP4.5), there is no evidence of increasingly longer dry spells, despite a significant rise in temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, there are conflicting opinions regarding whether the observed warming is inducing an increase in the length of dry spells, as noted by Ye and Fetzer (2019) in Russia, or whether, as observed by Trenberth et al, (2014), the warming does not prolong the dry event, but that the warming itself may augment the intensity of the episode due to the effect of thermal magnitude. The authors consider that the observed warming has not caused longer-lasting droughts in the area of the Pyrenees, which does not correspond with the findings of Ye and Fetzer (2019). Furthermore, even under an intermediate emissions scenario (RCP4.5), there is no evidence of increasingly longer dry spells, despite a significant rise in temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Since the presence of monotonic trend in the time series infers a "Shifted Mean" condition (i.e., an increase in the probability distribution) (Ye and Fetzer 2019), if the trend in the time series is found to be significant, then the location parameter of the GEV distribution, µ is modelled assuming a linear function of time (Katz 2013;Cheng et al 2014), while scale and shape parameters are assumed to be time-invariant.…”
Section: Modelling Of Compound Heat Stress-dry Spell Driversmentioning
confidence: 99%
“…The length of dry periods can directly reflect the degree of drought and is often used to assess drought conditions (Ye and Fetzer, 2019; Zhang et al ., 2019a). A long dry period leads to insufficient precipitation and causes serious drought, which has adverse effects on agricultural production, vegetation growth, and human society (Huth et al ., 2000; Tao et al ., 2009; Zhang et al ., 2015; Ye, 2018).…”
Section: Introductionmentioning
confidence: 99%